PENGARUH PENAMBAHAN JAGUNG GILING TERHADAP KUALITAS DAN KECERNAAN IN VITRO SILASE DAUN KETELA KARET (Manihot glaziovii) - , WURYAN GANDI HASTOMO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimed was to find out the effect of meal corn used at ceara rubber leaf silage making on in vitro quality and digestible. Milled corn used as additive on ceara rubber leaf silage that consist of all the leaf and steam. Three treatments of additional milled corn level in this research were 0%, 4%, and 6% of dry matter. Observed data were smell, colour, texture, pH, proximate analysis, NH3, HCN, and in vitro digestibility. Chemical compositions were rough fibre, rough fat, rough protein, and ash, along with in vitro test. Data of proximity, HCN, NH3, and digestibility obtained were analyzed by completely randomize design. Meanwhile, the data of pH were analyzed by randomized complete block design (RCBD). If only there were differences, the analysis was continued by using Duncanâs multiple range test (DMRT). Both of the RCBD and DMRT were using SPSS programme 18.0. The average of counting results toward the value of KcBK digestibility with the addition of milled corn 4% and 6%, in series, were 59.36Â±6.35